Kekhasan dan Keanekaragaman Bahasa dalam Tafsir Lokal di Indonesia - Irsyad Al Fikri Ys (UIN Sunan Gunung Djati Bandung, 2021)
The interpretation of the al-Qur'an, which is written using various characters and languages, proves the archipelago's ulama for the indigenous values contained in the holy verses of the al-Qur'an the public. In this place, the interpretation is written. However, at a certain level, in the environment of Indonesian interpretation, the model of interpretation which uses a certain language, ultimately cannot escape its elitist nature. It is because works in specific languages are only easily understood by the Muslim community who use that language, from the exposure of the background. This article aims to show in general the diversity of languages contained in local interpretations in Indonesia. Such as the uniqueness and cultural values that characterize local interpretations in the archipelago. The method applied in this article is descriptive-analytical. This article's research will describe the characteristics of local interpretations with elements of uniqueness and diversity of language in the interpretation. Among the peculiarities of the language in interpretations in Indonesia are vernacular, the term indigenous interpretation, and the wisdom of local languages in interpretation in Indonesia.